2022
DOI: 10.1002/ece3.9248
|View full text |Cite
|
Sign up to set email alerts
|

Molting phenology of a lacustrine ringed seal, Pusa hispida saimensis

Abstract: After the last glacial period, when the ice had retreated around 9500 years ago, ringed seals (Pusa hispida) were trapped in Fennoscandian lakes (Nyman et al., 2014). Today, ringed seals (P. h. saimensis) in Lake Saimaa differ morphologically, genetically, and behaviorally from their sister populations (Kunnasranta et al., 2021;Nyman et al., 2014;Peart et al., 2020). The endemic Saimaa ringed seal is classified as endangered according to the International Union for the Conservation of Species with a current po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…While males hauled out around the clock with a slight preference for daytime, females continued to have a peak in the haul-out during nighttime. A correlation between air temperature and the number of molting females has been described before (Niemi et al, 2022), and this could at least partly explain the difference in the haul-out patterns between the sexes during the molt. Diel rhythm can be defined as rhythmic alterations in physiological processes that enable the prediction of the changes in light and dark cycles, which allows mammals to perform their activities at the optimal time (Güldür & Otlu, 2017).…”
Section: Re Sultsmentioning
confidence: 65%
See 3 more Smart Citations
“…While males hauled out around the clock with a slight preference for daytime, females continued to have a peak in the haul-out during nighttime. A correlation between air temperature and the number of molting females has been described before (Niemi et al, 2022), and this could at least partly explain the difference in the haul-out patterns between the sexes during the molt. Diel rhythm can be defined as rhythmic alterations in physiological processes that enable the prediction of the changes in light and dark cycles, which allows mammals to perform their activities at the optimal time (Güldür & Otlu, 2017).…”
Section: Re Sultsmentioning
confidence: 65%
“…Camera traps enabled monitoring during the molting season, while the tags, which are glued to pelage, drop off due to weakening of the bond to the hair or at molt at the latest. In this study, the last tag dropped off at the second week of April (Table S1), before the peak of the molting season (Niemi et al, 2022). The game cameras (N = 50 in 2012 and N = 63 in 2013, Scout Guard 550VB and 560K-8M with 2-4 GB memory cards) were deployed on trees or wooden planks placed in the vicinity of observed haul-outs.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also increasingly recognized that species change their diel patterns throughout the year. For example, Niemi et al (2023) found diel haul-out patterns of the lacustrine Saimaa ringed seal (Pusa hispida saimensis) change markedly between seasons, switching from nocturnal to diurnal depending on the availability of ice and the seals' moulting phase. By exploring the full spectrum of activity patterns, we can gain a more comprehensive understanding of species' ecological roles, interspecific interactions, and responses to human-mediated disturbance (Cox & Gaston, 2023).…”
Section: Introductionmentioning
confidence: 99%